2018
DOI: 10.1007/978-3-319-91287-5_24
|View full text |Cite
|
Sign up to set email alerts
|

Broadband NIRS Cerebral Cytochrome-C-Oxidase Response to Anoxia Before and After Hypoxic-Ischaemic Injury in Piglets

Abstract: Perinatal hypoxic ischaemic (HI) encephalopathy is associated with severe neurodevelopment problems and mortality. This study uses broadband continuous-wave near-infrared spectroscopy (NIRS) to assess the early changes in cerebral oxygenation and metabolism after HI injury in an animal model using controlled anoxia events. Anoxia was induced before and 1 h after various levels of HI injury to assess the metabolic response via the changes in the oxidation state of cytochrome-c-oxidase (oxCCO), a marker of oxida… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 13 publications
(13 reference statements)
0
3
0
Order By: Relevance
“…With appropriate selection of light wavelengths, fNIRS characterization of neurovascular coupling can be expanded to also include metabolic function, for example using cytochrome c oxidase (CCO) (Bale et al, 2018;Holper and Mann, 2018;Lange et al, 2019). Coupled with the ability to simultaneously measure fNIRS together with other neuroimaging analysis techniques such as EEG and neural network learning (Yang et al, 2019) fNIRS has the potential for widespread clinical applications in neuroscience.…”
Section: Introductionmentioning
confidence: 99%
“…With appropriate selection of light wavelengths, fNIRS characterization of neurovascular coupling can be expanded to also include metabolic function, for example using cytochrome c oxidase (CCO) (Bale et al, 2018;Holper and Mann, 2018;Lange et al, 2019). Coupled with the ability to simultaneously measure fNIRS together with other neuroimaging analysis techniques such as EEG and neural network learning (Yang et al, 2019) fNIRS has the potential for widespread clinical applications in neuroscience.…”
Section: Introductionmentioning
confidence: 99%
“…Given the small concentration of CCO in the brain and confounding by competing for absorption by hemoglobin, CCO measurement has only recently become practical. Broadband NIRS has been demonstrated in piglet models of HIE [ 37 ] as well as pilot studies of human neonates with HIE [ 35 , 38 ].…”
Section: Equipmentmentioning
confidence: 99%
“…So far, these biomarkers were focused on either cerebral oximetry using multidistance NIRS or broadband NIRS (bNIRS) or diffuse correlation spectroscopy (DCS) 6 . bNIRS brain tissue measurements of the oxidation state of Cytochrome -coxidase (oxCCO) have shown that it can reveal information on brain injury severity 7,8,9 . In this study, we present an assessment of the severity of HIE using optical data captured by FLORENCE, an integrated hybrid broadband near infrared spectrometer (bNIRS) and diffusion correlation spectrometer (DCS) instrument and a machine learning pipeline based on k-means clustering for classification.…”
Section: Introductionmentioning
confidence: 99%